Early oocyte triggering followed by in vitro maturation is a good approach in women with resistance ovary syndrome: A case-series - Maryam Eftekhar; Banafsheh Mohammadi; Nasim Tabibnejad; Mohammad Hossein Razi (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Background: Some women represent the inability to respond to endogenous and exogenous gonadotropins during in vitro fertilization/intracytoplasmic sperm injection cycles leading to the follicular developmental arrest. The women with resistant ovaries could benefit from in vitro maturation. Case: This case-series presents pregnancies resulting from initially scheduled conventional in vitro fertilization which led to arrested cycles because of resistant ovary syndrome. The protocol was changed to early oocyte triggering for 15 women due to the small follicles ≤ 12 mm in diameter on day 15 after stimulation with high doses of exogenous gonadotrophins instead of cycle cancellation. Germinal vesicle and metaphase I oocytes that were retrieved from follicles were matured in vitro and inseminated by intracytoplasmic sperm injection. Twenty formed embryos were transferred on day 3 after oocyte retrieval. This resulted in a 30.76% chemical pregnancy out of which no abortion occurred. Therefore, we reported a 30.76% singleton ongoing pregnancy. Conclusion: It seems that early oocyte triggering followed by in vitro maturation may be considered as a good modality in women experiencing follicular resistance to gonadotropins. These cycles can be rescued from cancellation with satisfactory clinical outcomes.